Swift heavy ion induced electron emission from solids. (June 2015) - Rothard, Hermann; Lanzanò, Gaetano; Gervais, Benoit; De Filippo, Enrico; Caron, Michel; Beuve, Michael
Abstract: We briefly summarize the results of numerous experiments performed at GANIL aimed at measuring electron yields and doubly differential yields (energy or velocity spectra at different ejection angles, angular distributions). These studies, supported by theoretical investigations and numerical simulations, contributed decisively to our understanding of the very first step in energy deposition in matter, i.e. ionization and subsequent electron transport through condensed matter. The emitted electron spectrum contains a rich variety of features including binary encounter electrons (BEE), convoy electrons (CE), Auger electrons (AE) and the low-energy peak of "secondary" electrons (SE).